1991
DOI: 10.1002/jnr.490290208
|View full text |Cite
|
Sign up to set email alerts
|

Possible neurotransmitter role of noradrenaline in the teleost retina

Abstract: The role of dopamine as a neurotransmitter in the retina of different species has been clearly established; however, there is still some controversy as to whether noradrenaline (NA) is present as a neurotransmitter in this tissue. In this study, we show that, under controlled conditions, NA is present in the retina of goldfish at a concentration of 0.15 +/- 0.03 ng/mg protein and its biosynthetic enzyme, dopamine beta-hydroxylase shows an activity of 2.5 +/- 0.2 pmol NA/hr/mg protein. The amount of NA increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…postsynaptic receptors located at the ganglion cells without directly influencing ganglion cell activity. These data are comparable to the teleost retina where DA and NE act as neuromodulators of intercellular signal transmission [Dowling and Ehinger, 1978;Osborne, 1981;Dowling, 1986;Jaffe et al, 1991;Baldridge et al, 19931. With this study we provide first evidence for establishing both DA and NE as potent neuromodulators in the trout pineal gland.…”
supporting
confidence: 73%
“…postsynaptic receptors located at the ganglion cells without directly influencing ganglion cell activity. These data are comparable to the teleost retina where DA and NE act as neuromodulators of intercellular signal transmission [Dowling and Ehinger, 1978;Osborne, 1981;Dowling, 1986;Jaffe et al, 1991;Baldridge et al, 19931. With this study we provide first evidence for establishing both DA and NE as potent neuromodulators in the trout pineal gland.…”
supporting
confidence: 73%
“…In humans, dopamine antagonists may suppress both a-and b-waves and prolong their implicit times (Bartel et al, 1990) or reduce b-wave amplitude only (Holopigian et al, 1994). Though there is no solid evidence that the overall amount of retinal dopamine is affected following several days in constant darkness (Jaffe et al, 1991;Manglapus et al, 1999), this does not mean that its turnover is not decreased, as shown by the decrease of its metabolites after transition from LL to DD (Doyle et al, 2002).…”
Section: Rod Erg Following Four Days In Darknessmentioning
confidence: 91%
“…GABA tonic release, suppressing rod function, is greater in darkness (Boatright et al, 1994); norepinephrine disappears in darkness (Jaffe et al, 1991), and the number of VIPþ cells declines linearly in darkness (Herbst & Thier, 1996). However, as far as we know, none of these neurochemicals has been studied with regard to the rod ERG.…”
Section: Rod Erg Following Four Days In Darknessmentioning
confidence: 94%